Getting Funding: Analysis of Challenges and Opportunities for Creative Startups in Indonesia - Pedro Silva; Clara Mendes; Thiago Rocha (Yayasan Adra Karima Hubbi, 2024)
Creative startups in Indonesia have become key players in the country's economic growth, contributing significantly to job creation and innovation. However, securing funding remains a major challenge for these startups. The gap in access to financing and the lack of understanding of investors about the creative sector often hinder the growth potential of these businesses. Despite the promising prospects, these challenges require a comprehensive analysis to identify the opportunities for overcoming funding barriers. This study aims to analyze the challenges faced by creative startups in Indonesia when seeking funding and explore the opportunities available to facilitate their access to capital. The research focuses on identifying key obstacles and evaluating potential solutions that could improve the startup ecosystem in the country. A mixed-methods approach was employed, combining qualitative interviews with creative startup founders and quantitative surveys conducted among investors and funding bodies. Data was analyzed to identify common challenges and potential opportunities within the funding landscape. The study found that limited awareness among investors, a lack of tailored financial products, and the perception of high risk associated with creative startups were the primary challenges. However, there are emerging opportunities, including government initiatives and the growing popularity of crowdfunding platforms, which are becoming viable alternatives for funding. To enhance the growth of creative startups in Indonesia, both government and private sectors must collaborate to provide more accessible and specialized funding options. Additionally, increasing awareness among investors about the potential of the creative sector can unlock new funding opportunities.